ANALISA NILAI KEKASARAN PERMUKAAN MATERIAL BAJA AISI 4340 PADA PROSES PERMESINAN BUBUT CNC DENGAN METODE TAGUCHI - Ariandi_saputra; Muhammad Subhan; Indah Riezky Pratiwi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The results of the minimum surface roughness in the MORI SEIKI SL-25 CNC machining process, the parameters of the MORI SEIKI SL-25 CNC machining process are adjusted in order to obtain a minimum workpiece surface roughness reaction. The research that has been tried aims to ensure the contribution of the CNC MORI SEIKI SL-25 machining process parameters to reduce the alteration of the workpiece surface roughness reaction simultaneously. As well as setting the right parameters of the CNC MORI SEIKI SL-25 machining process parameters in order to obtain a minimum workpiece surface roughness. The machining process parameters that were varied were cutting speed, feed depth and feed motion. The experimental design was inaugurated based on the Taguchi method and in the form of an orthogonal matrix L9 (33). The analysis used is Taguchi. Experiments were carried out randomly with 3 replications to overcome the obstacles that occurred during the machining process. The research results show that to reduce the alteration of the response simultaneously, the cutting speed has a value of 61.98%, the depth of feed has a value of 16.28%. And eating motion has the smallest value of -12.45%. To obtain a minimum workpiece surface roughness on AISI 4340 steel with the MORI SEIKI SL-25 CNC machining process, the cutting speed is set at 130 m/min, the feed depth is set at 1.0 mm and the feed motion is set at 0.55 mm/put.